Hybrid renewable energy: Mobile micro hydro turbine / Yeo Jue Chuan - Yeo, Jue Chuan (2018)
The HRES (Hybrid Renewable Energy System) involves combination of two or more renewable energy sources, or mixed with conventional sources to make a new set of power generation. The combination can be any blend of renewable sources. The renewable energy sources in the nature is always facing an intermittent predicament. To overcome and ameliorate the issues, hybrid combination with storage (aka battery) Semiconducting Magnetic Energy Storage (SMES), water storage as potential for hydro turbine implemented in the invention of HRES. Mobile Micro Hydro Turbine and the energy supply by photo voltaic (PV) make this research project as a HRES by moving the gearbox and lifting water to storage tank through two sets of piston pumps and a long arm connected to gearbox for reducing force. The optimum sizing method for stand-alone HRES, introduces an optimum size of battery bank, using SMES and excessive energy convert to storage water as hydro power generation. This is to maximize the components for power generation and also to incorporate the DPSP (Deficiency of Power Supply Probability) and the LCC (Life-cycle Cost). It also can achieve technical and economical application by the system reliability. The PRA (power reliability analysis) is so important when come into the design process inclusive of satisfy load demand and calculate the cost effective in economic aspect. To apply the cost analysis for HRES, some economic criteria is required. The Net present cost is involved the installation works and the energy levelised cost. The levelised cost is the ratio of the total yearly system cost to the yearly electricity supplied by the system and LCC (life-cycle cost) of the components installed.